KNOWLEDGE OF NUTRITION - HEALTH REPRODUCTION AND ITS ASSOCIATION WITH RISKY BEHAVIOR AMONG 15-19 YEARS OLD ADOLESCENTS - Susanti, Rosa; Siti Fatimah, Okta Zenita (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
This study aims to describe the relationship between knowledge of balanced nutrition and reproductive health among adolescents and their engagement in risky behaviors. The research method used was a survey conducted with a randomly selected group of adolescents aged 15-19 years. The results indicated that most adolescents have limited knowledge of balanced nutrition and reproductive health. However, the findings also showed a positive relationship between knowledge of balanced nutrition and healthy eating behaviors, while a negative relationship was found between knowledge of balanced nutrition and risky behaviors such as the consumption of fast food and alcoholic beverages. Knowledge of reproductive health also proved to be significant, with adolescents possessing better knowledge being more likely to avoid risky reproductive health behaviors, such as unprotected sex. In conclusion, this study provides insights into the importance of knowledge about balanced nutrition and reproductive health in shaping adolescent behaviors and highlights the need to enhance their understanding through appropriate educational programs and interventions